Lendas para cantar: uma análise dialógica do discurso das canções amazônicas de Waldemar Henrique - Oliveira, Patrick Paiva de [UNESP] (2015)
Based on concepts that integrate the theoretical and reflective mesh developed by the Bakhtin Circle, this study aims to understand how Brazilian art song was constituted while literarymusical genre in the early twentieth century through the analysis of the art songs which belong to the cycle Lendas Amazônicas composed by Waldemar Henrique. The art songs, for voice and piano, are registered in scores and integrate this set. They were produced between the 1930s and 1940s, when the artistic and cultural events were promoted by economic policy introduced by Vargas and serve as advertisement to the consolidation of a nationalist discourse. This work also aims to understand how the myths and legends of oral literature are incorporated and re-elaborated in the production of the songs from the established reciprocal relationship between the primary and secondary genres. Our work methodology is qualitative in nature and aims (through dialectic-dialogical approach) to describe, analyze and interpret the songs. Since our research object is composed of heterogeneous semiotic plans, our analysis will be performed in two main levels: the verbal and the musical only by methodological character. The song will be understood as an ideological sign that has a dual materiality (at least) - verbal (poem lyrics) and the music (implemented by the musical elements that constitute it: melody, harmony, rhythm, accompaniment etc.)